Intervention of carbohydrate recognition by proteins and nucleic acids. - Sears, P (1996)
Carbohydrates in biological systems are often associated with specific recognition and signaling processes leading to important biological functions and diseases. Considerable efforts have been directed toward understanding and mimicking the recognition processes and developing effective agents to control the processes. The pace of discovery research in glycobiology and development of carbohydrate-based therapeutics, however, has been relatively slow due to the lack of appropriate strategies and methods available for carbohydrate-related research. This review summarizes some of the most recent developments in the field, with particular emphasis on work from our laboratories regarding the use of chemoenzymatic strategies to tackle the carbohydrate recognition problem. Highlights include the study of selectin-carbohydrate and aminoglycoside-RNA interactions and development of agents for the intervention of these recognition processes.